2018
DOI: 10.1007/s11081-018-9376-7
|View full text |Cite
|
Sign up to set email alerts
|

Wing aerodynamic optimization using efficient mathematically-extracted modal design variables

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Abstract Aerodynamic shape optimization of a transonic wing using mathematically-extracted modal design variables is presented. A novel approach is used for deriving design variables using a singular value decomposition of a set of training aerofoils to obtain an efficient, reduced set of orthogonal 'modes' that represent typical aerodynamic design parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…However, the sectional deformations can also be applied in a global nature, and while this is not as flexible as local deformation, the authors have shown global deformations to provide reasonable optimization results but at a fraction of the cost. 23 The sectional deformations are applied using the RBF control point approach, where a set of control points are defined in the fluid domain and global volume interpolation translates deformation of the control points to deformation of the aerodynamic mesh. Hence, the modal deformations are used to drive deformation of the control points that subsequently deform the wing surface and mesh.…”
Section: Iib Application To Wing Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sectional deformations can also be applied in a global nature, and while this is not as flexible as local deformation, the authors have shown global deformations to provide reasonable optimization results but at a fraction of the cost. 23 The sectional deformations are applied using the RBF control point approach, where a set of control points are defined in the fluid domain and global volume interpolation translates deformation of the control points to deformation of the aerodynamic mesh. Hence, the modal deformations are used to drive deformation of the control points that subsequently deform the wing surface and mesh.…”
Section: Iib Application To Wing Deformationmentioning
confidence: 99%
“…These are applicable to aerodynamic optimization of aerofoils 5 and wings. 23 Furthermore, comprehensive experiments 24 have shown singular value decomposition (SVD) modes to be the most efficient approach at representing a generic aerofoil compared to most other commonly used parameterization methods.…”
Section: Introductionmentioning
confidence: 99%
“…Modal deformations are applied sectionally at ten spanwise station (on the red main control points), while intermediate control points (shown in blue) are used to permit smooth spanwise deformations between the deformation slices. 35 The deformation of intermediate points uses a partition of unity-blend of the deformation slices at either side. A global twist deformation is also introduced.…”
Section: Iva2 Application To Wing Deformationmentioning
confidence: 99%
“…Of these, singular value decompositionbased approaches take a training matrix of data (for example a number of aerofoil shapes [24,25]), and project a reduced-order basis approximation of the original data. Work by the authors has shown that this is a very efficient approach for producing a reduced set of aerofoil deformation modes [26] that are suitable for aerodynamic optimization of aerofoils [6] and wings [27]. The reduced set of modes has been used for high-fidelity global optimization of aerofoils [6].…”
Section: Introductionmentioning
confidence: 99%